2019
DOI: 10.2174/0929867325666180406120051
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AMPK in Diabetes and Diabetic Complications: Energy Homeostasis, Autophagy and Mitochondrial Health

Abstract: Adenosine 5'-monophosphate activated protein kinase (AMPK) is a key enzymatic protein involved in linking the energy sensing to the metabolic manipulation. It is a serine/threonine kinase activated by several upstream kinases. AMPK is a heterotrimeric protein complex regulated by AMP, ADP, and ATP allosterically. AMPK is ubiquitously expressed in various tissues of the living system such as heart, kidney, liver, brain and skeletal muscles. Thus malfunctioning of AMPK is expected to harbor several human patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 105 publications
3
49
0
Order By: Relevance
“…AMPK plays a major role in cellular energy metabolism and redox homeostasis. Previous evidence suggested that AMPK activation can decrease reactive oxygen species (ROS) production and protect mitochondria biogenesis as well 21. A significant reduction in the p-AMPK / AMPK protein ratio was detected in diabetic mice compared with that in controls by immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…AMPK plays a major role in cellular energy metabolism and redox homeostasis. Previous evidence suggested that AMPK activation can decrease reactive oxygen species (ROS) production and protect mitochondria biogenesis as well 21. A significant reduction in the p-AMPK / AMPK protein ratio was detected in diabetic mice compared with that in controls by immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Reductions of the mitochondrial membrane potential in podocytes cultured in HG was alleviated after Sirt6 plasmid transfection. AMPK is a highly conserved cellular bioenergetic sensor that contributes to the regulation of multiple cellular functions ranging from energy homeostasis to cell death regulation21. Growing evidence has suggested that AMPK signaling malfunction is proved to have pathological implications in mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK is highly expressed in renal cells, such as podocytes, and plays a crucial role in maintaining glucose homeostasis (20). Previous studies have proposed a protective role for AMPK signaling in mitochondrial function (17,21,22). Notably, a decrease in the p-AMPK/AMPK protein ratio was witnessed in the diabetic rats, which prompted the investigation into the underlying role of sesn2 in AMPK regulation (Fig.…”
Section: Histopathological Features Of Glomeruli and Podocyte Injury mentioning
confidence: 99%
“…Notably, LPSinduced acute myocardial injury can be significantly attenuated by upregulation of autophagy (17,18). The activation of AMP-activated protein kinase (AMPK) signaling is effective in upregulating autophagy (19,20). It might be a promising way to alleviate LPS-induced acute myocardial injury via the activation of AMPK signaling, upregulation of autophagy, and suppression of inflammation.…”
Section: Introductionmentioning
confidence: 99%